Frozen Section-A Short Review - Ryhanath Gulshan1 , N. Aravindha Babu2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
rozen section is a specimen of tissue that has been quick-frozen, cut by microtome, and stained immediatelyfor rapid diagnosis of possible malignant lesions. A specimen processed in this manner is not satisfactory fordetailed study of the cells, but it is valuable because it is quick and gives the surgeon immediate informationregarding the malignancy of a piece of tissue. Frozen section plays an important role in the management ofsurgical patients yet it must be used prudently to avoid the indiscriminate usage of this important technique.As it is subjected to many limitations compared to the paraffin embedded tissue sections, this reviewhighlights the important concepts and principle of intra-operative frozen section consultation as well asdiscussing the limitations of this technique.